Effects of tropical fruit peels on in vitro rumen fermentation profiles and gas production in cattle - Othman, Athira Amanina (2016)
Feed is one of major factor that plays important role in the animal production cost. Basic nutrition itself contributes in main expenses. There are various studies that have been done in order to reduce the feed cost by improving the nutritive value in the feedstuffs. In tropical countries, the abundance of tropical fruit peel is seen as an opportunity to explore new utilization of these waste products. Since most of tropical fruits are not seasonal, it becomes one of the advantages to run this study. There are four types of fruit peels chosen to be used in this study. Banana peels, pineapple peels, papaya peels and mangosteen peels are collected in the area near the UPM area. A study on nutritive value of banana peels, pineapple peels, papaya peels and mangosteen peels was conducted via in vitro rumen fermentation. Proximate analysis was also done to analyze the nutrient content in the samples. The general objective of this research was to determine the response of the rumen environment with different tropical fruits peel in cattle via in vitro rumen fermentation analyses. Diet 1 is banana peels sample, diet 2 is pineapple peels sample, and diet 3 is papaya peels sample while diet 4 is mangosteen peels sample. All these samples had 3 replicates. All these samples were added to basis diet as supplement. The basis diet consists of rice straw and concentrate. All the results were compared to the control diet’s result. After 24 hours period of in vitro rumen fermentation, the gas production of all samples are not significant (P<0.05) to the control’s results. There are differences in cumulative gas production data, but there were no significant differences according to statistical analysis. After gas production procedure, rumen fluid residues of samples were tested for pH reading. The pH readings of rumen fluid from all fruit peels supplement diets after in vitro procedure were also not significant (P<0.05) when compared to pH value of rumen fluid for control’s diet. The rumen fluid residues after the gas production procedure were collected for volatile fatty acid (VFA) analysis. The acetate, butyrate and propionate acid results were not affected (P<0.05) when added with the fruit peels supplement diets when compared to control’s result. Even though gas production, final rumen fluid’s pH reading and VFAs production are not significant when compared to control diet, but ammonia production results of pineapple peels supplement diet and papaya peels supplement diet are significantly decreasing (P<0.05) when compared to control diet. But the ammonia gas production was not affected (P<0.05) when banana peels supplement diet and mangosteen peels supplement diet are used. For recommendation, further studies are needed in order to utilize this fruit waste. In future, some modification may be needed in this case for further study. For example, another type of fruit peels can be used. The percentage of fruit peels used can also be varied. Last but not least, the fruit peels used can be modified or treated. Thus, fruit peels can be used as a supplemental diet in ruminant as it has not significantly changes most at the crucial fermentation profiles.